PANAMA PAPERS DAN FENOMENA PENYELUNDUPAN PAJAK SERTA IMPLIKASINYA TERHADAP PENERIMAAN PAJAK INDONESIA - Chairil Anwar Pohan (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
Leakage of 11.5 million the biggest financial document file unprecedented from Mossack Fonseca database which is the fourth largest law firm based in Panama in charge of tax-free or tax-exempt business. These files contain about how famous people and rich hide their wealth from the obligation to pay taxes. In total, this leak contains information about more than 214 thousand tax-exempt entities connected to rich people in more than 200 countries (including quite a lot from Indonesia who evade taxes numbering in the thousands trillion, approximately 899 people and companies in Indonesia, which became the company off shore and became a shareholder and director of the off shore company (tempo.co.id) is hidden in tax haven countries.